Italian Society of Interventional Cardiology (GIse) registry Of Transcatheter treatment of mitral valve regurgitaTiOn (GIOTTO): impact of valve disease aetiology and residual mitral regurgitation after MitraClip implantation. (29th March 2021) - Bedogni, Francesco; Popolo Rubbio, Antonio; Grasso, Carmelo; Adamo, Marianna; Denti, Paolo; Giordano, Arturo; Tusa, Maurizio; Bianchi, Giovanni; De Marco, Federico; Bartorelli, Antonio L.; Montorfano, Matteo; Godino, Cosmo; et al.
Abstract: Aims: The Italian Society of Interventional Cardiology (GIse) registry Of Transcatheter treatment of mitral valve regurgitaTiOn (GIOTTO) was conceived in order to assess the safety and efficacy of MitraClip therapy in Italy. The aim of this study was to assess procedural and mid‐term outcomes, and clinical and echocardiographic predictors of mid‐term mortality after MitraClip therapy, stratifying the results according to the diagnosis of functional and degenerative mitral regurgitation (FMR vs. DMR). Methods and results: Between January 2016 and March 2020, 1659 patients were prospectively included in the GIOTTO registry (FMR 59.4% vs. DMR 40.6%). Acute Mitral Valve Academic Research Consortium (MVARC) technical success was achieved in 97.2% of patients, without differences between FMR and DMR and with sustained results at 30 days. In the study population, all‐cause mortality was 4.0%, 17.5% and 34.6% at 30 days, 1 year and 2 years, respectively. Cardiovascular death was the most frequent cause of mortality. Overall hospitalization rates were 6.3%, 23.4% and 31.7% at 30 days, 1 year and 2 years, respectively. The most frequent cause of hospitalization was heart failure, particularly in the first 30 days. FMR and MVARC structural and functional failure were strongly associated with 1‐year mortality. Residual mitral regurgitation 1+ (rMR) was independently related to a reduced risk of 1‐year mortality (hazard ratio 0.62; P  = 0.005). Coherently, at 2‐year follow up, FMR was associated with worse outcomes than DMR, and Kaplan–Meier all‐cause mortality was related to rMR. Conclusions: Functional mitral regurgitation aetiology affects 1‐year mortality after MitraClip implantation, and differences in mortality and hospitalization rates between FMR and DMR can be observed within 2 years. Optimal rMR 1+ was correlated to a more favourable mid‐term outcome, particularly in FMR.